Curriculum Transformation for The Relevance of Education to Global Developments and The Needs of Society in The Contemporary Era - Fuadi (al-Afkar, Journal For Islamic Studies, 2024)
Curriculum transformation is crucial in ensuring the relevance of education to global developments and the needs of society in the contemporary era. Curriculum transformation allows Education to become more adaptive, interactive, and relevant to technological developments and society. This type of research leads to qualitative research based on literature research both print and digital. Discriptive analysis method used is This analysis helps in describing, demonstrating, or helping to summarize data points. A transformed curriculum can prepare students with skills needed in an ever-evolving world of work, such as critical thinking, creativity, collaboration, and problem-solving skills. In addition, curriculum transformation allows for personalized learning, where each student can learn according to his own pace, learning style, and interests. Therefore, curriculum transformation contributes positively to student development in facing changes and complexities of life in the contemporary era.